Pengaruh Health Literacy Berbasis Augmented Reality terhadap Peningkatan Pengetahuan tentang Persiapan Kehamilan - Wahyuni, Nur Ismi; Futriani, Elfira Sri; Himawan, Himawan; SR, Nurqalbi (Madu Jurnal Ilmu Kebidanan, 2025)
Some women of childbearing age who are preparing for pregnancy are still unaware of nutritional issues that greatly affect the preconception period, often prospective brides or mothers will be ignorant of the nutritional content of food intake, therefore the number of KEK is still relatively high. The development of health promotion media in the form of Augmented Reality applications is expected to increase interest in the material presented. With increased interest in the material, then the subsequent knowledge of understanding will experience an increase. The purpose of this study was to determine the effect of Health Literacy preconception preparation and screening based on Augmented Reality on Women of Childbearing Age. The research method used a Randomized controlled trial design with two groups PreTest - PostTest Design. A total of 50 Women of Childbearing Age who have never given birth. The research instrument was a questionnaire that will later be processed to obtain results. The study used Unity 3D software which is an alternative application that can be used in creating Augmented Reality. The results of the study showed that the knowledge of the participants before being given Augmented Reality was 62.6 and after being given Augmented Reality intervention, the results of the intervention were 82.3. Based on the Wilcoxon test, the results were assessed with a p value of 0.000 < 0.005. This result shows that there is an influence of Augmented Reality-based Health Literacy on increasing knowledge about pregnancy preparation in fertile women in 2025.